Cutaneous mastocytosis: Clinical Case - Aset Kh. Ibisheva; Madina R. Shakhgireeva; Linda V.-M. Dzhabrailova; Asya B. Khildikharoeva; Linda S. Uspanova; A. A.-R. GetaevaKamila (Педиатрическая фармакология, 2024)
Skin syndrome is common in the practice of allergologist-immunologist, and it requires differential diagnosis. One of the rare skin diseases among children is mastocytosis caused by excessive accumulation of mast cells in various organs. Cutaneous Mastocytosis is the most common form in children. The disease onset may occur at any age. The pathognomonic symptom of mastocytosis is positive Darier sign. The presented clinical case demonstrates typical picture of cutaneous mastocytosis.